Zapomniane uczone Uniwersytetu Poznańskiego: doc. dr hab. Wisława Knapowska – nauczycielka i historyczka (7.06.1889-8.05.1956) - Głowacka-Sobiech, Edyta (Studia Edukacyjne, 2018)
The text introduces the figure of Wisława Knapowska, one of the first independent scholars of Poznań University, a researcher and teacher of the best schools in the interwar period. It shows her path to academic independence and the many barriers she encountered in her life. The text is part of the socalled herstory, asking for the past and history of women’s narratives.